A capacitação dos instrutores do programa educacional de resistências às drogas e à violência – PROERD/AM a partir das concepções sobre a sua formação e aplicação do programa - Henriques, Alisson Da Silva (2023)
Objective: Identify the training needs of Proerd Instructors, their profile professional, using as a basis their own information and conceptions to build the ostensibly excellent policing and efficient and effective prevention of drugs and violence, through a training course. Methods: The research was carried out in dialogue with the inductive method, from the particular to the general, based on questions or focuses of interest broad that became more direct and specific during the investigation, in which the Qualitatively oriented researcher plans to develop theory about what he studies, measure that collects and examines data. As it is a qualitative research, the case study was employed due to the expansion of the concept that can be understood as a family or a small group that are the Proerd Amazonas Instructors. The data analysis technique qualitative studies involved content analysis, in this context the needs were mapped training and the identity of Proerd Instructors, as well as the process of preparing a periodic training course, after defining the contents to be reinforced, to be acquired, frequency of ongoing training and how it should be formatted, given the achieve the proposed objectives. Results: The Resistance Educational Program Drugs and Violence – Proerd has 84% ​​of Military Police officers in its workforce male and 16% female. Regarding the age range of this workforce, it is highlighted that 24% were is between 29 and 39 years old, 68% between 40 and 50 years old and 8% over 50 years old. What does it say Regarding academic training, the percentage of 4% discriminates that only a professional do not have a higher education degree, 28% have a degree in Pedagogy and other degrees predominantly in the area of ​​Human Sciences. Considering taking a course update, based on the Curricular Mesh for Training Actions of the Civil and Military Police (Common Core), and also the specific part of working in a drug prevention program, the disciplines were ordered according to the priorities established by the Police Officers Military, Proerd Instructors.Final Considerations: The Professional Training Course, as a technical-technological product, it came to systematize what was already foreseen as Proerd Pedagogical Week, albeit empirically, as it is held annually carried out, with professionals linked and integrated into the Institution's activities, as stipulated by CAPES. Therefore, research has value in the sense of knowing the fields mandatory descriptions and comply with them, with due academic and scientific zeal, so that may have due recognition in the Corporation and be followed by other Units that seek training. Training courses are an instrument of public policy for training and professional development, which is why they must be presented through guiding documents, and not simply cited as a way to improve the provision of a service and/or customer service to the public.